2015
DOI: 10.1021/jp510542x
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Circular Dichroism of Nicotine in Aqueous Solution: A Test Case for Continuum and Mixed Explicit-Continuum Solvation Approaches

Abstract: In this paper, we extend an integrated QM/MM/polarizable continuum model (PCM) method, which combines a fluctuating charge (FQ) approach to the MM polarization with the PCM, to describe electronic circular dichroism (ECD) spectra of systems in aqueous solution. The main features of the approach are presented, and then applications to the UV and ECD spectra of neutral (S)-nicotine in aqueous solution are reported. The performance of the QM/FQ/PCM is compared with that of the PCM against newly measured UV ECD sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 34 publications
(68 citation statements)
references
References 70 publications
(133 reference statements)
3
65
0
Order By: Relevance
“…Also, implicit solvation is accurate enough to reproduce the OR and other chiroptical spectroscopies of aqueous solutions of (S)‐ N ‐acetylproline amide, where explicit solute–solvent interactions are in principle expected. A different situation occurs for nicotine in aqueous solution, where the inclusion of specific solvation effects leads to an improvement in calculated Electronic Circular Dichroism (ECD) spectra, though continuum solvation yields qualitatively correct results, as well as reasonable OR values in isopropanol …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, implicit solvation is accurate enough to reproduce the OR and other chiroptical spectroscopies of aqueous solutions of (S)‐ N ‐acetylproline amide, where explicit solute–solvent interactions are in principle expected. A different situation occurs for nicotine in aqueous solution, where the inclusion of specific solvation effects leads to an improvement in calculated Electronic Circular Dichroism (ECD) spectra, though continuum solvation yields qualitatively correct results, as well as reasonable OR values in isopropanol …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that such a limitation can be successfully overcome by moving to QM/MM/continuum approaches, such as the recently developed fully polarizable QM/FQ/PCM method with nonperiodic boundary conditions, which includes polarization effects in the classical MM portion by means of fluctuating charges (FQ) and resorts to a continuum PCM treatment of the outer solvation shell. In particular in this model the solvated molecular system is decomposed in three layers, in a multiscale fashion (Figure ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equilibrium between the charge interactions and the differences in the atomic electronegativities represents the physical basis of the electronegativity equalization principle, which defines, in turn, the FQ model. The QM/FQ model has recently been extended by some of the present authors to the evaluation of analytical first and second derivatives, response equations, magnetic perturbations with gauge independent atomic orbitals (GIAO) and excitation energies at the equation of motion coupled cluster singles and doubles (EOM‐CCSD) level, and has been shown to give remarkable agreement with experimental findings in various applications in the field of computational spectroscopy . In the polarizable QM/FQ approach, the interaction energy is analogous to eq.…”
Section: Theorymentioning
confidence: 72%
“…As a matter of fact, full QM approaches become in this case not only unfeasible unless resorting to oversimplified (e.g., semiempirical) methods, but also quite illogical, whenever the interest is not to reach a detailed description of the whole solvent, but, rather, of the tuning of solute structure and/or properties by the solvent. For this reason, focused models, that is, strategies paying privileged attention to the solute, seem the methods of choice and several reports suggest that, among different alternatives, QM/MM models are especially effective . Solvent effects on the solute structure and/or properties are tuned by a subtle interplay of short‐ and long‐range contributions.…”
Section: Introductionmentioning
confidence: 99%